KARBON TERSIMPAN PADA BERBAGAI TIPE KERAPATAN TEGAKAN DI HUTAN RAKYAT DESA SUKOHARJO I KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU - Dio Ivando; Irwan Sukri Banuwa; Afif Bintoro (Forestry Study Program University Of Mataram, 2019)
Forests had an important role in carbon reserve and uptake: where this was one of efforts of global warming’s impacts mitigation. The aim of this research was to know the effect of density in potential of carbon reserve and uptake in the private forest. Data collection was carried out by survey; then the collected data were analyzed for tree biomass, necromass, litter and ground plants, total of carbon stock in one area, suitability of carbon stock, CO2 absorbtion, and the differences in carbon stock and carbon uptake in each of density class. The result showed that, forests with low density were significantly lower in stored carbon and CO2 absorption, respectively 54.57 tons/ha and 200.27 tons/ha. In medium and high density forests, both the amount of stored carbon and CO2 uptake were no different. At medium density, stored carbon was 79.78 tons/ha, and CO2 absorption was 292.79 tons/ha. In high density, stored carbon was 92.94 tons/ha and CO2 absorption was 341.09 tons/ha.